(2-Methyl-3-nitrophenyl)methanol - Zhang, Jian-hong (International Union of Crystallography, 2009)
The asymmetric unit of the title compound, C(8)H(9)NO(3), contains two crystallographically independent molecules, whose aromatic rings are oriented at a dihedral angle of 83.29 (3)°. In the crystal structure, intermolecular O—H⋯O hydrogen bonds link the molecules into chains.